Preferential retention of algal carbon in benthic invertebrates: Stable isotope and fatty acid evidence from an outdoor flume experiment. (2nd March 2020) - Kühmayer, Thomas; Guo, Fen; Ebm, Nadine; Battin, Tom J.; Brett, Michael T.; Bunn, Stuart E.; Fry, Brian; Kainz, Martin J.
Abstract: According to the River Continuum Concept, headwater streams are richer in allochthonous (e.g. terrestrial leaves) than autochthonous (e.g. algae) sources of organic matter for consumers. However, compared to algae, leaf litter is of lower food quality, particularly ω‐3 polyunsaturated fatty acids (n‐3 PUFA), and would constrain the somatic growth, maintenance, and reproduction of stream invertebrates. It may be thus assumed that shredders, such as Gammarus, receive lower quality diets than grazers, e.g. Ecdyonurus, that typically feed on algae. The objective of this study was to assess the provision of dietary PUFA from leaf litter and algae to the shredder Gammarus and the grazer Ecdyonurus . Three different diets (algae, terrestrial leaves, and an algae–leaf litter mix) were supplied to these macroinvertebrates in a flume experiment for 2 weeks. To differentiate how diet sources were retained in these consumers, algae were isotopically labelled with 13 C. Both consumers became enriched with 13 C in all treatments, demonstrating that both assimilated algae. For Gammarus, n‐3 PUFA increased, whereas n‐6 PUFA stayed constant. By contrast, the n‐3 PUFA content of Ecdyonurus decreased as a consequence of declining algal supply. Results from compound‐specific stable isotope analysis provided evidence that the long‐chain n‐3 PUFA eicosapentaenoic acid (EPA) in both consumers was more enriched in 13 C than the short‐chain n‐3 PUFA α‐linolenic acid, suggesting that EPA was taken up directly from algae and not from heterotrophic biofilms on leaf litter. Both consumers depended on algae as their carbon and EPA source and retained their EPA from high‐quality algae.